Bond length (Ti-O) dependence of nano ATO(3)-based (A = Pb, Ba, Sr) perovskite structures: Optical investigation in IR range - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2018)
In the current study, ABO(3) (A = Pb, Ba, Sr and B = Ti) perovskite structures are produced by the auto-combustion route by using citric acid (CA) and nitric acid (NA) as fuel and oxidizer. The X-ray diffraction (XRD) patterns confirmed the perovskite nanostructure with cubic, tetragonal, and rhombohedral for SrTiO3, PbTiO3, and BaTiO3, respectively. Using Scherrer's equation and XRD pattern, the average crystallite size of the samples were acquired. The effect of Ti-O bond length on the structure of the samples was evaluated. The type of structures obtained depends on Ti-O bond length which is in turn influenced by A(2+) substitutions. Microstructural studies of nanostructures calcined at 850 degrees C confirmed the formation of polyhedral particles with a narrow size distribution. The values of optical band gaps were measured and the impact of A(2+) was discussed. The optical properties such as the complex refractive index and dielectric function were calculated by IR spectroscopy and Kramers-Kronig (K-K) relations. Lead, as the element with the highest density as compared to other elements, changes the optical constants, remarkably due to altering titanium and oxygen distance in TO6 groups.
Keywords: Perovskite system; X-ray diffraction; TiO2-based-NPs; bond length; complex optical properties; KRAMERS-KRONIG; AUTO-COMBUSTION; THIN-FILMS; NANOPARTICLES; NANOPOWDERS; CERAMICS; COMPOSITE; SPECTRA; PHASE; SIZE